Chile : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper describes economic developments in Chile during 1990-95. In part, as a result of the tight monetary policy introduced in early 1992, real GDP growth declined from 11 percent in 1992 to 6 percent in 1993 and further to about 4 percent in 1994. The monetary stance was gradually eased starting in October 1994, and output growth rebounded to 6.6 percent in the first quarter of 1995 compared with the same period of the previous year. Nevertheless, the 12-month rate of inflation fell to 7.9 percent in July 1995.